ok first you have to distribute on each side, remember to watch the (-) (+) signs.
- 4 (x + 2) - 11 = 2 (- 2x -3) - 13
_________________________
-8x + (-8) - 11= - 4x -6 - 13
now that you are done distributing the 4 and 2, you must start isolating the X's, I like the x on the left, and so will work it that way. it makes no difference though....if you like it on the right, that is fine too. so I will start with the 4, and remember whatever you do to one side you must do to the other.
-8x + (- 8) - 11 = -4x - 6 - 13
+4x +4x
__________________________
-4x + (-8) -11= - 6 -13
remembering you cannot subtract with positive and negative numbers so be careful of the signs and change/change the subtraction to plus signs. so let's do that next.
-4x + (-8) + (-11)= -6 + (-13 )
now that you have changed the signs as above, do the operations on both sides.
-4x + (-19) = (-19)
now yo umust further isolate the X, so move the (-19) from left to right, again what you do to one side you must do to the other.
-4x + (-19) = (-19)
+19 + 19
________________
-4x = 0
now divide out the -4, which into zero is zero, therefore x= 0, thus any number plugged in for the x would result in an "x=0" answer.
hope this helped, for more help ask yahoo answers, or try www.purplemath.com, it is a great math site!
2006-11-10 15:10:10
·
answer #1
·
answered by trish the dish 3
·
0⤊
0⤋
X=0
2006-11-10 14:33:13
·
answer #2
·
answered by jtruitt82 1
·
0⤊
0⤋
Thats actually an easy mathmatical equation....... All you have to do is use the distributing property, cancel out and either solve for "x" or make sure there equal on both sides....
4(x+2)-11=2(2x-3)-13
4x+-8-11=4x-6-13
+13 +13
4x+-8+2=4x-6
+8 +8
4x+2=4x+2
divide the 4 by 2 and x=2
"I THINK"
2006-11-10 14:30:42
·
answer #3
·
answered by shanaycain2000 2
·
0⤊
0⤋
-4x-8-11=-4x-6-13
-8-11=-6-13
-19=-19
Infinite Solutions
2006-11-10 15:02:48
·
answer #4
·
answered by abcde12345 4
·
0⤊
0⤋
-4(x + 2) - 11 = 2(-2x - 3) - 13
-4x - 8 - 11 = -4x - 6 - 13
-19 = -19
the "-4x" 's cancel each other out so you are left with
-19 = -19
2006-11-10 14:44:39
·
answer #5
·
answered by trackstarr59 3
·
0⤊
0⤋
first multiply -4 with x&2
so u will get -4x-8-11
now add up -11&-8=-19
now this is in the left of the equation -4x-19
the equation in the rigt becomes
-4x-6-13
-4x-19
now solve both
-4x-19=-4x-19
-4x=-4x
x=1
2006-11-10 14:30:24
·
answer #6
·
answered by aishu 1
·
0⤊
0⤋
x = 1
-4(x+2)-11=2(-2x-3)-13
-4x - 8 - 11 = -4x - 6 - 13
-4x - 19 = -4x - 19
-4x = -4x + 0
-4x = -4x
x = 1
2006-11-10 14:28:57
·
answer #7
·
answered by SPCnut 3
·
0⤊
0⤋
-4(x+2)-11=2(-2x-3)-13
-4x-8-11= -4x-6-13
0x-8-11= 0x-6-13
0x-19= 0x-19
0x/0= 0/0
x=1
2006-11-10 15:12:45
·
answer #8
·
answered by CK 3
·
0⤊
0⤋
The equation is true. No matter what number you put in, the equation is true. If zero, -19 = -19. If 10, -59 = -59.
2006-11-10 14:37:13
·
answer #9
·
answered by Chemist Chris 2
·
0⤊
0⤋
-4X - 8 - 11 = -4X + 39
-4X+ 4X = 39 + 8 + 11
0X = 58
X = dos not exist
2006-11-10 14:25:28
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋